COST EFFECTIVENESS ANALYSIS ON THE CONTROL OF HEPATITIS C VIRUS INFECTION TRANSMISSION DYNAMICS - S. A. ABDULLAHI; A. M. GAZALI; ADAMU ISHAKU, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
In this paper, we proposed a mathematical model for hepatitis C virus (HCV) transmission dynamics. The cost and health benefits of various control strategies for preventing and curtailing the spread HCV infection were assessed via a computational approach. The MATLAB solver ODE45 is used to examine the impact of each strategy on the total number of infected individuals over the planning horizon. It is found that epidemiological impact of the strategies revealed that strategy E which is combination of: enlightening the susceptible and recruit individuals, screening, counselling and treatment is the most effective. Furthermore, the cost effectiveness of each strategy in terms of Incremental Cost Effectiveness Ratio (ICER) is calculated using Quality Adjusted Life Years (QALYs) as health benefit. The result revealed that HCV can be controlled most efficiently by implementing strategy E as it gives a smaller number of infected individuals and is highly cost effective.